Draft estimates of expenditure for the year 1994 - Trinidad and Tobago. Ministry of Finance (Government printery, Trinidad and Tobago, 1994)
This report contains: 1) Abstract showing 1992 actual expenditure, 1993 estimates, 1993 revised estimates, 1994 estimates and variance +/() 1994 over/under the 1993 revised estimates. 2) Abstract of estimated expenditure for the year ending 31st December, 1994. 3) Abstract showing sums provided in 1994 estimates but excluded from Appropriation Bill, 1994.
Keywords: Government expenditure